Deism in enlightenment England Theology, politics, and Newtonian public science. - Wigelsworth, Jeffrey R. (Manchester : Manchester University Press, 2009)
This is the first complete study of English deists as a group in several decades and it argues for a new interpretation of deism in the English Enlightenment. While there have been many recent studies of the deist John Toland, the writings of other contemporary deists have been forgotten. With extensive analysis of lesser known figures such as Anthony Collins, Matthew Tindal, Thomas Chub, and Thomas Morgan, in addition to unique insights into Toland, *Deism in Enlightenment England * offers a much broader assessment of what deism entailed in the eighteenth century. Readers will see how previou.
9780719078729; 9780719078729; Copyright Page; Contents; Acknowledgements; Abbreviations, dates, and quotations; Introduction: the importance of deist theology; Chapter 1: The meaning of 1689: politics and theology, 1694 -1700; Chapter 2: The issue of succession: politics and theology, 1701-09; Chapter 3: Matter, motion, and Newtonian public science, 1695-1714; Chapter 4: The spectre of High Church:politics and theology, 1709-19; Chapter 5: Matter, motion, and Newtonian public science, 1720-41; Chapter 6: The age of Walpole: politics and theology, 1720-41; Conclusion: radical no more.
BibliographyIndex.
Description based on print version record.
Keywords: Deism -- England -- History -- 18th century; England -- Religion -- 18th century; Deism -- England -- History -- 18th century; England -- Religion -- 18th century; RELIGION / Deism; Electronic books